THE PRINCIPLES OF SAUL KRIPKE’S AND HILARY PUTNAM’S SEMANTICS AND THEIR INFLUENCE ON THE CONTEMPORARY ANALYSIS OF LEGAL LANGUAGE - SZCZEKOCKI, Piotr (Comparative Legilinguistics, 2010)
The conception of Saul Kripke‘s and Hilary Putnam‘s semantics belongs to new semantic concepts. It formulates three principles which have an essential influence on the contemporary analysis of a law language. Statements which can be inferred from this concept indicate: 1. The independence of the language meaning of a law text from a historical legislator‘s intention, attaching significance on the practice of the phrases used in a given communicative community. 2. The influence of various ways of a language law use on the procedure of establishing its meaning. 3. The evolution in time of the language meaning of a law text. Saul Kripke‘s and Hilary Putnam‘s semantics tries to prove that a law interpretation process, being compliant with the principles of the law positivism, whose characteristic feature is the linguistic character of the law, should consider the changes in time of a law text meaning, the arguments of an unbinding precedent, the views formulated by a doctrine or the comparative arguments. As a result, it is to make them treated as the arguments for establishing the meaning of the law text phrases. This concept pays attention to the context in which language is used and it focuses on the language community which a speaker belongs to.